Self-Care Management Education Using a Pocketbook on Illness Perception Improvement in Psoriasis Patients - Fatma, Endah Panca Lydia; Sari, Dewi Purnama; Windarwati , Heni Dwi; Susanto, Akhiyan Hadi; Rohmadani, Dewi (Jurnal Kedokteran Brawijaya, 2025)
Psoriasis is an autoimmune disease affecting the integumentary and organ systems. It impacts daily activities and degrades self-esteem. Meanwhile, there is a minimum amount of literature about self-care management education for Psoriasis. Pocketbooks can be used as an alternate learning tool for self-care management by making them more portable among patients. The aims are to foster a positive perception of illness and self-determination regarding Psoriasis. This study evaluated the effectiveness of providing self-care management education using a pocketbook on the illness perception of Psoriasis. The research employed a mixed-methods design, combining quasi-experimental and qualitative approaches. The study involves 30 participants diagnosed with Psoriasis. Participants are divided into two groups: a control and an intervention group. The Brief Illness Perception Questionnaire (B-IPQ) was utilized to assess the participants' perceptions of their illness before and after the intervention. A paired t-test was used to compare pre-test and post-test scores within each group. A two-sample t-test was employed to compare the mean differences between the control and intervention groups. The significance level was set at a p-value of 0.05. The interview data were transcribed verbatim using thematic analysis. The study indicates a difference in the illness perception of patients between control and intervention groups with a significance value of 0.000. Patients report that understanding triggers and management strategies allow for better health. Pocketbook is a practical education approach improving illness perceptions of Psoriasis. Recognizing triggers and adopting management techniques, patients are able to take steps to deal with flare-ups and improve their well-being.